ASSESSMENT TECHNIQUES IN PROJECT-BASED LEARNING CLASS - Khotia, Nur Aqsho (2018)
This research was aimed at finding the ways selecting and designing the assessment techniques which were chosen to assess the students. The descriptive qualitative method was employed in this study. The data were obtained through document and observation as the instruments of the research. The study showed the techniques in assessing students through Project-Based Learning activity. The assessment techniques were crucial in teaching-learning. Assessment of project-based learning often focus much of their attention on the product of the learning experience. Based on the findings, the result indicated that, even though not all teachers used the assessment techniques, there were four assessment techniques namely 1) observation assessment, 2) project work assessment, 3) performance-based assessment, and 4) traditional test (paper-pencil test). Those assessment techniques helped teachers assess the students in implementing project-based learning activity. This study recommends teachers to be more aware of and be prepared in assessing their students. ;---Penelitian ini bertujuan untuk mengetahui cara memilih dan merancang teknik penilaian yang dipilih untuk menilai siswa. Metode kualitatif deskriptif digunakan dalam penelitian ini. Data diperoleh melalui dokumen dan observasi sebagai instrumen penelitian. Penelitian ini menunjukkan teknik dalam menilai siswa melalui kegiatan Pembelajaran Berbasis Proyek. Teknik penilaian sangat penting dalam pembelajaran. Penilaian pembelajaran berbasis proyek sering kali banyak memusatkan perhatian mereka pada produk pengalaman belajar. Berdasarkan temuan tersebut, hasilnya menunjukkan bahwa walaupun tidak semua guru menggunakan teknik penilaian, ada empat teknik penilaian yaitu 1) penilaian observasi, 2) penilaian pekerjaan proyek, 3) penilaian berbasis kinerja, dan 4) uji tradisional ( tes pensil kertas). Teknik penilaian tersebut membantu guru menilai siswa dalam melaksanakan kegiatan pembelajaran berbasis proyek. Studi ini merekomendasikan agar guru lebih sadar dan siap dalam menilai siswa mereka.